Moral Values of Movie “Ghostbuster: Afterlife” - Marvino Christian; Fauziah Nur (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
This research aims to describe the moral values found in the movie “Ghostbuster Afterlife